2010
DOI: 10.1186/bcr2728
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for the generation of genetically modified mammary epithelial cell cultures yields new insights into TGFβ signaling in the mammary gland

Abstract: IntroductionMolecular dissection of the signaling pathways that underlie complex biological responses in the mammary epithelium is limited by the difficulty of propagating large numbers of mouse mammary epithelial cells, and by the inability of ribonucleic acid interference-based knockdown approaches to fully ablate gene function. Here we describe a method for the generation of conditionally immortalized mammary epithelial cells with defined genetic defects, and we show how such cells can be used to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Thus, the MAPK pathway interacts in important ways with the SMAD pathway. However, SMAD activation is an important component of the cytostatic response to TGF-β, as indicated by the effects of small molecule inhibition of the TβR-1 kinase (Seay et al 2005), SMAD3 knockout cells (Kohn et al 2010) and dominant-negative SMAD3 mutants (Liu et al 1997). …”
Section: Modulation Of Tgf-β Signals In the Vascular Environmentmentioning
confidence: 99%
“…Thus, the MAPK pathway interacts in important ways with the SMAD pathway. However, SMAD activation is an important component of the cytostatic response to TGF-β, as indicated by the effects of small molecule inhibition of the TβR-1 kinase (Seay et al 2005), SMAD3 knockout cells (Kohn et al 2010) and dominant-negative SMAD3 mutants (Liu et al 1997). …”
Section: Modulation Of Tgf-β Signals In the Vascular Environmentmentioning
confidence: 99%
“…Such cell lines appear to retain many biological properties of the cells from which they were derived, including gene expression patterns and response to signalling pathways (Kohn et al, 2010). We derived two sets of cell lines from dissected E10.5 forelimb buds to represent the most posterior third of the distal limb (cell lines P1 and P2) or the anterior two-thirds (A1 and A2) (Fig.…”
Section: Image Analysismentioning
confidence: 99%
“…Furthermore, in vitro studies have shown that Smad2 and Smad3 have unique functions in mammary epithelium and oncogenesis, in which Smad3 and not Smad2 is critical to inducing TGFβ-mediated apoptosis, cell cycle arrest and EMT. 18,19 …”
Section: Tgfβ and Smad Signalingmentioning
confidence: 99%